Effectiveness and Outcome of Electronic Medical Record in Patient Service: A Systematic Review - Turido Pratama (Medical Scope Journal, 2024)
Abstract: Using electronic medical records is one endeavor to enhance healthcare services and patient outcomes. The electronic medical record (EMR) is employed in healthcare facilities to accomplish every objective. This studyaimed to  evaluate the effectiveness and effect of medical record usage in hospitals. This was a systematic review study. Three databases—PubMed, ScienceDirect, and Cochrane—were searched for research publications in this study. Publications published during the last ten years were targeted for search. Three reviewers were involved in the screening of the title and abstract to establish eligibility. Information was acquired from the studies included in this systematic review using a data extraction form that had been pilot tested. The results obtained a total of 1341 articles selected through a search process by entering keywords in a predetermined database. Articles based on inclusion and exclusion criteria were selected, so that, seven articles were included in this study. Most of the studies indicated that EMR benefited health workers to give better clinical performances to the patients, improving quality-adjusted life year (QALY) of the patients, and reduce the mortality rates. In conclusion, implementing the EMR system may benefit health workers and increase their hospital performance. Keywords: electronic medical record; outcome; hospital; health workers